"Les femmes n'ont pas le droit!": Social and legal exclusions of female artisanal coltan miners in eastern Democratic Republic of the Congo. (December 2022) - Furniss, Allison
Highlights: Women face social exclusions to mine work based on perceptions of femininity vs masculinity that, blended with economic factors, push women into more precarious work environments. Women's work in ASM is largely concentrated in the 'small trader position' that largely falls in-between legal categories, pushing women's contributions to the coltan production chain to the periphery. There is a gap between the legal permit categories that govern ASM in DRC and women's actual work in mining, contributing to the invizibilization of women's work in mining. Misinterpretation of the law by mine site authorities unfairly targets female miners on parameters of motherhood that negatively impacts women economically. This article pushes back on regional dominant narratives and centers women's lived experiences. Abstract: Despite active involvement in artisanal coltan mining in eastern Democratic Republic of the Congo (DRC), women face specific gendered exclusions from mine work based on social and legal parameters. Based on three months of ethnographic fieldwork in multiple artisanal coltan mine sites in Masisi Territory in the province of North Kivu, this study employs ethnographic observations, focus group and formal and informal interview methodologies. In the highly independent and fluctuating environment of artisanal mining, women frequently work in buying, washing, refining and reselling small quantities of coltan, providing meager profits but important livelihood strategies. However, localized social norms surrounding notions of femininity and masculinity concentrate women's work in more precarious positions, even when profits are similar to men. Women working in this context are also often caught 'in between' legal binaries in the state mine permit system, invisibalizing women's work and pushing women's labor contributions to the periphery. In addition, mine site authorities' misinterpretation of the law that seeks to protect children from working in the mines, negatively impacts breastfeeding mothers who subsequently are chased out of the mines and loose valuable time on-the-job. Lastly, pregnant women also face gendered vulnerabilities, frequently targeted and coerced based on motherhood. This article seeks to describe and analyze these gendered exclusions and intersections with women's gendered vulnerabilities which all hinder economic prosperity.